Experimental study on flocculation performance of Chitosan-Based Flocculant using a Novel Jar Tester - Kazuhiro Fujisaki (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2018)
The effectiveness of chitosan as a flocculant was tested with a novel experimental apparatus. Using a newly developed flocculation tester, a large number of flocculation rate processes were measured. The novel jar tester included a photocoupler and switching timer. Mixing was paused for a period and the floc-settling velocity and residual turbidity were measured during this period. The relation between the turbidity of the supernatant (i.e., the residual turbidity) and chitosan dose was measured over a wide range of initial turbidities. The chitosan showed two windows for the optimum dose: (1) a dose close to that used with ordinary inorganic flocculants, at which the residual turbidity showed complicated behavior under the influence of various factors, and (2) an optimum dose in the order of 10−4 of the initial turbidity. The latter optimum-dose range is very narrow, and simple chargeneutralization plays an important role in the flocculation.